PANGGUNG SEJARAH TERBENTUKNYA KABUPATEN PASANGKAYU: SEBUAH STUDI PUSTAKA - Rahmadi U (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
This study aims to examine the historical stages of the formation of Pasangkayu Regency through a literature review approach. The main focus of this study is to investigate the historical, social, political, and administrative dynamics underlying the region's formation as an autonomous region. This study is a library research, which mainly gathering and analyzing various relevant sources from history records, government documents, scientific journals, and archives related to the regional expansion process. The study's findings indicate that the formation of Pasangkayu Regency was inseparable from the aspirations of local communities seeking improved public services, accelerated development, and strengthened regional identity. Furthermore, geographic factors, natural resource potential, and strategic government considerations played an important role in the regional expansion process from its parent region. This process involved a lengthy process, from the discourse of expansion, administrative struggles, to official determination by the central government. The formation of Pasangkayu Regency resulted from a complex interaction between historical, social, and political factors that developed at the time. This study is expected to enrich the local historical studies for further research on the dynamics of regional expansion in Indonesia.